Concept Religiousity At Islamic Education In Modern Era - Putri Anggi Nauli; Kiki Puspita Dewi (Proceeding International Seminar of Islamic Studies, 2019)
Research about religiousity concept to islamic education in era modernisation. Problem that appear is in era modernisation right now all of inclined character work wide and individual. Wherever should to islamic education able increase individual quality with involve value that mean to concept religiousity for overcome inclination society so that good produce the generation strong belief,individual sturdy,and intelektual sturdy. What is concept religiousity at islamic education in era modernisation have close relationship.the purpose of this research is to find out.What is the concept of religiousity on islamic research in the modern era.right now the method used is library research.and qualitative method the importance of understanding religiousity in islamic education in the face up to globalisation era right now.because religion is a way of life that contains rules that must be practiced in the order to be able to change and shape into insanul kamil.